IMPROVING STUDENTS' VOCABULARY USING SONG MULTIMEDIA AT THE THIRD YEAR OF SD MUHAMMADIYAH PROGRAM KHUSUS BOYOLALI IN 2009/2010 ACADEMIC YEAR - NUGRAHENI , SARWO SRI (2010)
This study is aimed at describing the procedures of teaching vocabulary using song multimedia, its influence of implementation song multimedia to the students' vocabulary mastery, and explaining the strengths and weaknesses of implementation song multimedia in teaching vocabulary. In achieving the objective of the study, the researcher used an action research involving four stages; planning, implementing, observing, and reflecting. This research was held in SD Muhammadiyah Program Khusus Boyolali. The writer took 26 students in the third grade as the sample of the research. To collect the required data, she uses observation, interview, and test. After collecting and analyzing the data, the result of this research is as follows: 1) 20 students or 76,9 % increased their vocabulary achievement, 1 student of 3,8 % is static, and 5 students or 19,2 % decreases. 2) The strengths of this research, the students are interested and motivated in learning English using song multimedia, while the weaknesses are the English teacher must spend her spare time at home to prepare some materials, the English teacher not only focused in explain the material, but also the English teacher has operated some devices. The students got difficulty to catch the native speaker pronunciation. It can be concluded that teaching vocabulary using song multimedia in SD Muhammadiyah Program Khusus Boyolali has a good result. The use of song multimedia in teaching vocabulary is effective. The students' achievement increased, and the students' response is good.